[Are Facebook Ratings Associated with Hospital Quality and Patient Satisfaction? A Cross-Sectional Analysis of Obstetrics Care in German Hospitals]. - Emmert, Martin; Becker, Sandra; Meszmer, Nina; Sander, Uwe (Gesundheitswesen, 2018)
Social media websites, such as Facebook, have been gaining popularity. Little is known about the usefulness of such online ratings when searching for a hospital. We therefore assessed the association between online Facebook ratings and clinical quality of care measures as well as patient satisfaction for German hospitals in obstetrics care. (1) We identified all German hospitals providing services in obstetrics care based on the German external quality assurance system (2015) and gathered relevant data. (2) Based on a structured dialogue, we determined quality of care results for all hospitals and (3) assigned them to 3 different performance groups. (4) We collected Facebook online ratings as well as (5) patient satisfaction (Patients' Experience Questionnaire, PEQ) results for all included hospitals. (6) We applied the Spearman rank coefficient of correlation. We could find a Facebook page for almost all of the included hospitals (728/752; 96.8%). Facebook hospital ratings in general were mostly positive, especially in obstetrics care. There was no association between Facebook hospital ratings (ρ=0.007; p=0.860) or those for obstetrics care (ρ=0.008; p=0.856) and clinical quality of care measures. In contrast, we could detect an association between Facebook ratings and patient satisfaction scores. The association was stronger for overall hospital ratings (ρ=0.383-0.543; p<0.001) than those for obstetrics care (ρ=0.111-0.250; p<0.05) in particular. So far, Facebook online ratings are of limited usefulness in guiding patients towards high-performing hospitals from a clinical point of view. However, our findings suggest that Facebook ratings may serve as an indicator of patient satisfaction when searching for hospitals. OBJECTIVE METHODS RESULTS CONCLUSION